Case-based reasoning research and development : 23rd International Conference, ICCBR 2015, Frankfurt am Main, Germany, September 28-30, 2015, proceedings /: 23rd International Conference, ICCBR 2015, Frankfurt am Main, Germany, September 28-30, 2015, proceedings. (2015) - Unknown
No abstract available